Fluctuations in Inflation and Matching with Experimental Data - Năstase, Horaţiu [UNESP] (My University, 2019)
In this chapter we will show how to calculate the spectrum of fluctuations during inflation, and relate that to observables. We will quantize fluctuations during inflation, and show what power spectrum they give, and how that reflects into the CMBR fluctuations. The final point will be how to then constrain various inflationary models using experimental data.